Tourist Perceptions of Beach Cleanliness in Barbados: Implications for Return Visitation - Peter W. Schuhmann (Études Caribéennes)
The quality of the natural environment is inexorably linked to tourism in the Caribbean. Tourists are attracted to the beauty of the Caribbean coastal and marine environment, generating significant economic activity and employment. The resulting development and concentration of human activities in the coastal zone may have deleterious effects on environmental quality and tourists’ willingness to return. Using a survey administered to over 2,000 tourists in Barbados, this work examines tourist perceptions of beach quality and encounters with beach litter. The relationship between the quality of the coastal environment and the probability of return visitation is empirically investigated. Results demonstrate a clear link between viewing beach litter and the perceived quality of beaches and that tourists who stayed beachfront or in large hotels encountered significantly less beach litter and had higher ratings of beach quality. The amount of litter viewed and stated perceptions of beach quality are significantly associated with the probability of return visitation, especially for first-time visitors. Results of this study suggest that targeted beach clean-up efforts may enhance the probability of return visitation and create significant economic value.